The Equipping Church ; Guide book - Mallory, Sue (Zondervan, 2001)
Like a building site well-stocked with quality raw materials, your church abounds with possibilities--life-changing ministries just waiting to be developed. The Equipping Church Guidebook shows you how. Refining and expanding groundbreaking material, this in-depth approach helps you identify, equip, and empower lay ministers who will profoundly influence your church and your community. Behind this volume lies a massive body of research on hundreds of equipping churches across the country. Now you and your leadership team can reap the benefits with this exhaustive, hands-on resource. Nothing else compares with it. Designed and field-tested by today’s leading architects of equipping ministry, Leadership Training Network, The Equipping Church Guidebook is a blueprint for custom-building the systems and culture that are ideal for your church. Part one, Building an Equipping Ministry Vision and Culture, explains what an equipping church is, walks you through the conceptual stages, and helps your church transition to equipping vision and values. Part two, Building an Equipping Ministry System, helps you lay relational and strategic foundations, and then build on them an equipping system that gives structure and effectiveness to every aspect of church life. The Equipping Church Guidebook includes * Detailed information, clear instructions, and helpful examples * Abundant charts, graphs, and diagrams * Worksheets and assessment forms to help you apply the concepts in this book * Practical suggestions and checklists * "Contractors Conferences" to foster dialogue and decision-making as a leadership team Together with The Equipping Church, this guidebook helps you and your leadership team catch and implement the vision of Ephesians 4:11-13--equipping the saints for works of service that lead to spiritual maturity--in your church. One of the most challenging and exciting journeys in your church’s life lies ahead of you. Let the adventure begin!